Visualized analysis of research hotspots and evolution trends in the field of motivation in physical activity - Mingda Si; Chee Keng John Wang (Asian Journal of Sport and Exercise Psychology)
Physical activity (PA) is a green and effective way to maintain health. Research in the field of motivation in PA is always an important research topic for researchers and policymakers in maintaining public health, but few studies focus on the development of motivation in PA research. Summarize the research strengths, hotspots, and stages of scientific evolution in the field of motivation in PA by performing visualization analysis which used CiteSpace software on 2375 publications including from January 1st, 1980, to January 31st, 2024, in the Web of Science Core Collection (WOSCC). The findings are as follows: (1) Over the past thirty years, the field has developed rapidly, with current characteristics aligning with the third stage of the four-stage model of scientific evolution. (2) Core countries and core institutions have been formed, with the most influential country being the United Kingdom, and the most influential institution being Brown University. (3) The research hotspot focuses on intervention research in the field of motivation in PA under self-determination theory (SDT). This study provides researchers with an overview of the development in the field of motivation in PA research. It offers valuable information to researchers for identifying potential collaborators (institutions) and better positioning their research directions.